Implementasi Zakat Profesi Pada Profesi Advokat di Perhimpunan Advokat Indonesia (Peradi) Medan (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2022)
Professional zakat is income or income obtained from work such as: salaries of employees, consultants, doctors, advocates (lawyers), and others. Professional zakat issued by someone who works as a lawyer or advocate is something that will be an interesting problem to be written in this paper. And more specifically, a profession is a job or business that generates money or wealth, whether the work or business is carried out alone, without relying on other people, such as the government, private companies, or with individual wages, salaries or honorariums, so people who work as Advocates are also required to pay zakat. This type of qualitative research with a normative legal approach. Methods of collecting data by means of observation, interviews and documentation. Data analysis techniques include data reduction, data presentation and drawing conclusions. Reducing data means summarizing, choosing the main things, focusing on the important things, looking for themes and patterns. The presentation of the data is done in the form of a short description (narrative), charts, relationships between categories and the like. Through the presentation of data, the data is organized, arranged in a pattern of relationships, so that it will be easy to understand and draw conclusions. The result of this research is that Advocates' income can be seen from the classification. Payments can be divided into 3 (three) parts, including Lawyer fees, Operational fees, and Success fees. Payment systems usually offered by Lawyers/Advocates/Legal Consultants, based on processing time and payment procedures are usually divided into 5 (five) payment schemes: Lump sum/Wholesale, Hourly basis/Hourly Rate Perportion/Amount won by Permanent Clients/Institutional Retainer Legal Aid (LBH). The nisab limit for assets obtained from professional businesses can be equated with the nisab for gold and silver, which is 93.6 grams, with a 2.5 percent zakat obligation, which is issued every year, and after expenses are incurred, basic needs.